Kepemimpinan Sekolah dalam Situasi Krisis Covid-19 di Indonesia - Ali Murfi; Irwan Fathurrochman; Atika Atika; Nora Saiva Jannana (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2020)
Coronavirus disease (Covid-19) is shaking the world. This massive event triggered by infectious disease is beyond the predictions of many people, even practitioners, and experts in the field of crisis management. Now all sectors are affected, including the world of Education. Academic leaders respond by moving their educational activities and those related online. The decision to pivot into distance learning is made quickly. This research focuses on highlighting how the headmaster's leadership in carrying out crisis management in the Islamic School of Al-Azhar Cairo Yogyakarta by going through the stages, namely 1) Before the Crisis, 2) During the Crisis, 3) After the Crisis. This research uses a qualitative method with the type of case study. The results showed that Before the Crisis stage was carried out by implementing the Covid-19 Prevention Literacy policy. The stages during the crisis are carried out with (a) Health Talk, (b) Learning from Home Policy, and (c) Video and Podcast Challenge. After the crisis phase, the principal develops a collaborative approach to leadership, evaluating, and controlling the various effects of the crisis to prevent future crises. Crisis management is needed so that schools can be better prepared to deal with crises and reduce their impact so that the learning process and managerial activities can continue to run productively.